DISTANCE EDUCATION IN UKRAINE: REALITIES OF TODAY - Olha Zadorozhna ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The first attempts to introduce distance education technologies in the education sector were made in the 60s of the twentieth century in Western Europe and the United States. The rapid development of information technology and computerization of the population have led to an increase in demand for new, specific technologies in education, which allows applicants to study at considerable distances from educational institutions. It is the criteria to which the distance learning conforms, and which has been and remains the subject of active scientific discussion both abroad and in our country. Such a system of acquiring knowledge can significantly reduce the cost of education, as distance education is cheaper than traditional forms of higher education, and also reduces transport costs for travel to the place of study and back. Moreover, distance education can be obtained in any rhythm convenient for the applicant, distributing the workload at will. With the correct organization of classes and control of knowledge high efficiency of this method of professional education can be achieved through the use of new software and hardware platforms and electronic courses. On the other hand, critics of distance education say that its quality cannot be compared even with extramural education, and such educational technologies allow only to obtain a diploma with minimal investment of effort and resources without acquiring factual knowledge. The low quality of distance education, according to some experts, can be explained by the lack of quality methods of distance teaching, the average quality of e-courses, as well as the e-learning environments themselves.